Allergic Rhinitis is Associated with Open-Angle Glaucoma: A Population-Based Case–Control Study. Issue 4 (July 2014) - Chung, Shiu-Dong; Lin, Herng-Ching; Hung, Shih-Han
Background: Despite many reports linking allergic rhinitis (AR) to problems of the eye, the relationship between AR and open-angle glaucoma (OAG) has not been studied. The purpose of this epidemiology study was to provide an estimation of the association of OAG with AR by using a population-based data set in Taiwan. Methods: We retrieved our study sample for this case–control study from the Longitudinal Health Insurance Database 2000. We extracted 7063 subjects with OAG as cases and 21, 189 matched controls (three controls per case). We used conditional logistic regression analyses to calculate the odds ratio (OR) and corresponding 95% confidence interval (CI) to describe the association between OAG and having previously been diagnosed with AR. Results: A chi-squared test showed that there was a significant difference in the prevalence of prior AR between cases and controls (28.8% versus 22.3%; p < 0.001). A conditional logistic regression analysis suggested that the OR of having previously been diagnosed with AR for cases was 1.40 (95% CI, 1.31∼1.48; p < 0.001) compared with controls after adjusting for monthly income, geographic region, urbanization level, hypertension, diabetes, asthma, coronary heart disease, hyperlipidemia, and hypothyroidism. It also revealed that OAG was consistently and significantly associated with prior AR across all age groups. In particular, subjects aged 50∼59 years had the highest OR for prior AR among cases compared with controls (OR, 1.77; 95% CI, 1.53∼2.06; p < 0.001). Conclusion: This outcome research found that there was an association between AR and OAG.